2009
DOI: 10.1097/qad.0b013e32832b4449
|View full text |Cite
|
Sign up to set email alerts
|

Anal human papillomavirus infection is associated with HIV acquisition in men who have sex with men

Abstract: Objective Human papillomavirus (HPV) is a common sexually transmitted agent that causes anogenital cancer and precancer lesions that have an inflammatory infiltrate, may be friable and bleed. Our aim was to determine the association between anal HPV infection and HIV acquisition. Design A prospective cohort study. Methods We recruited 1409 HIV-negative men who have sex with men recruited from a community-based setting in Boston, Denver, New York and San Francisco. We used Cox proportional hazards regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 31 publications
(35 reference statements)
11
125
1
4
Order By: Relevance
“…131 Anal HPV infection was independently associated with HIV acquisition in the single included study that assessed anal infection among MSM. 132 Considerable uncertainty surrounds the natural history of HPV infection and clinical utility of testing among MSM at present. Thus regular testing for HPV in MSM is not recommended.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…131 Anal HPV infection was independently associated with HIV acquisition in the single included study that assessed anal infection among MSM. 132 Considerable uncertainty surrounds the natural history of HPV infection and clinical utility of testing among MSM at present. Thus regular testing for HPV in MSM is not recommended.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…Therefore, the observed association between persistent HR HPV and new HSV-2 infection warrant further studies and should be interpreted with caution. However, several studies have found that HPV infection increases the risk for HIV acquisition by 1.8 -3.5 times [32]- [34]. Lissouba et al (2013) in their meta-analysis review found that HR HPV infection was associated with almost a 2-fold increased risk for incident HIV infection, while LR HPV infection had only a borderline association [35].…”
Section: Discussionmentioning
confidence: 98%
“…2,3 La infección por VPH en HSH se asocia con una incidencia en cán-cer anal de 17 veces más que en los heterosexuales; 4 además de que su incidencia es más alta que las tasas de cáncer de cérvix en las mujeres, 5,6 pues estos últimos tienden a regresar a la normalidad después de los 30 años de edad. Ocurre lo contrario con los HSH, pues están en riesgo de lesiones anales y orofaringeas asociadas con VPH de células escamosas intraepiteliales a lo largo de su vida.…”
Section: Inmunización Contra El Virus De Papiloma Humano En Perú Másunclassified
“…Junior Smith Torres-Román, Est Med, (1,2) jstorresroman@gmail. Políticas públicas en salud basadas en la evidencia.…”
Section: 10unclassified